Personal and societal factors associated to student debt levels - O'Day-Stevens, Tamara, author; Anderson, Sharon K., advisor; Albert, Lumina, committee member; Carlson, Laurie, committee member; McKelfresh, David, committee member (Colorado State University. Libraries, 2014)
The purpose of this quantitative study was to explore the factors associated with the debt accumulation of students who are currently enrolled in graduate school at a public research university in the Rocky Mountain region of the United States. Factors were examined through the following four key research questions: (a) How much self-reported debt do graduate students accumulate during their undergraduate education? (b) What financial decision making factors uniquely contribute to total undergraduate debt accumulation as self-reported by graduate students? (c) What life impacting factors uniquely contribute to total undergraduate debt accumulation as self- reported by graduate students? and (d) What key demographic factors are associated with total undergraduate debt accumulation? A 17-question on-line survey, was administered to 3,852 students. The survey included demographic information and the following: overall debt, federal student loan debt, and credit card debt levels. To investigate whether low, medium, and high debt levels differ with attitudes towards using credit cards, federal loans, private loans, and loans for nonacademic expenses, individual Chi-Square tests were conducted. The research discovered that there was a relationship between attitudes towards: using credit cards (χ2=163.420, df = 8, N=772, p < .001), federal loans (χ2=290.741, df= 8, N=772, p < .001), and loans for nonacademic purposes (χ2=163.420, df = 8, N=772, p < .001) with overall debt levels. In addition, a relationship between debt level and academic major (χ2=21.447, df = 10, N=772, p <.018), and a relationship between debt level and age (χ2= 22.699, df = 2, N=772, p <.001), was also discovered. Multiple regression was conducted and the data analyzed indicated that there were three main factor associated to college debt levels, 17(1; Tuition and college cost), 17(5; Lack of support from my family) and 17(10; Not having good financial /money management skills). The combination of these variables to predict total debt was statistically significant, F (3,709) = 40.20, p < .001. Results of the current study contribute to the previous literature on student debt. Recommendations for future research and survey modifications were discussed.
Keywords: federal loans; credit card debt; student debt; academic debt; college debt